Tinjauan Yuridis Kasus Persamaan Merek Poskota dan Poskotaco (Studi Kasus Putusan No. 39 /Pdt.Sus-Merek/2022/PN Niaga Jkt.Pst) - Rahma, Arina Nafida; Mahmudah, Siti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Brand infringement case between POSKOTA owned by PT. Media Anatarkota Jaya and POSKOTACO owned by PT. Millennial Voice Media is listed in Court Decision No. 39 /Pdt.Sus-Merek/2022/PN Niaga Jkt.Pst, PT. Media Anatarkota Jaya (POSKOTA) as the aggrieved party sued for the cancellation of the PT. Media Suara Millenial (POSKOTACO). The object of the case in the decision is trademark infringement which is the same. The panel of judges granted the plaintiff's claim and ordered the defendant to cross out and cancel the registration of the POSKOTACO Mark. The purpose of this research is to find out the legal protection for trademarks that have been registered and the legal consequences of trademark equality disputes and to analyze the Decision of Court Decision No. 39 /Pdt.Sus-Merek/2022/PN Niaga Jkt.Pst. The approach method in this journal research is normative juridical by studying the Trademark Law and relating it to practice in the field. The results of this journal writing research are that brand owners who feel aggrieved due to parties who commit equality violations can apply for trademark cancellation based on the reasons in Articles 20 and 21 of Law Number 20 of 2016 Concerning Marks and Geographical Indications. The legal basis for the judge's consideration in deciding the trademark cancellation case is based on Article 76 jo. Article 20, Article 21 of Law Number 20 of 2016 concerning Marks and other relevant regulations.